HUBUNGAN PENGETAHUAN IBU, ASUPAN PROTEIN DAN ASUPAN ZINK DENGAN STUNTING (PENDEK) PADA BATITA USIA 12 – 36 BULAN - Juliyanti, Wike (JURNAL MEDIA KESEHATAN, 2014)
Stunting (short) is a chronic malnutrition can affect growth of infants and children due to inadequate food intake. The purpose of this study determine the relationship of mother's knowledge, the intake of protein and zinc with stunting (short) in toddlers aged 12-36 months. This study used a cross sectional design. The population is all children under the age of 12-36 months, the sample in this study amounted to 64 people the techniques used are systematic random sampling. Analysis of the data using chi square and logistic regresion test. The results showed that the mother's knowledge there is almost half of the respondents who are less knowledgeable about stunting, protein intake in children aged 12-36 months are almost half less, zinc intake in children aged 12-36 months are almost all respondents less, nutritional status of children 12-36 months of age are most of the stunting, there was no correlation between maternal knowledge and zinc intake with stunting in children aged 12-36 months, and there was association protein intake with stunting in children aged 12-36 months